2021
DOI: 10.1111/ivb.12319
|View full text |Cite
|
Sign up to set email alerts
|

Spawning, embryogenesis, settlement, and post‐settlement development of the gorgonian Plexaura homomalla

Abstract: Patterns of population biology and community structure can be studied by looking closely at the ontogeny and reproductive biology of reef‐building organisms. This knowledge is particularly important for Caribbean octocorals, which seem to be more resilient to long‐term environmental change than scleractinian corals and provide some of the same ecological services. We monitored the development of the black sea rod, Plexaura homomalla, a common, widely distributed octocoral on shallow Caribbean reefs, from eggs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…We observed elevated settlement approximately ten days after the full moon, which is approximately five days after predicted spawning for a number of octocoral species (Kahng, Benayahu, and Lasker 2011), indicating that octocorals prefer to settle as soon as they are competent. This timing matches the findings of Tonra, Wells, and Lasker (2021) and Lasker and Kim (1996), where Caribbean plexaurid octocorals took five days for median competency. Plexaurids are the most abundant family of octocorals that spawned during the time of this study (Kahng, Benayahu, and Lasker 2011).…”
Section: Discussionsupporting
confidence: 85%
“…We observed elevated settlement approximately ten days after the full moon, which is approximately five days after predicted spawning for a number of octocoral species (Kahng, Benayahu, and Lasker 2011), indicating that octocorals prefer to settle as soon as they are competent. This timing matches the findings of Tonra, Wells, and Lasker (2021) and Lasker and Kim (1996), where Caribbean plexaurid octocorals took five days for median competency. Plexaurids are the most abundant family of octocorals that spawned during the time of this study (Kahng, Benayahu, and Lasker 2011).…”
Section: Discussionsupporting
confidence: 85%
“…Previous work at Europa and Grootpan Bays found that newly metamorphosed Plexaura homomalla polyps that settled on unglazed stoneware clay tiles suffered 87% mortality over 59 d ( Martínez-Quintana & Lasker, 2021 ). Tonra, Wells & Lasker (2021) observed P. homomalla recruits reached three polyps (2–3 mm) in 10 weeks. If we assume recruits within the 0.3–0.5 cm size class were at least 1–2 months old, adding 1–2 months mortality would reduce our estimates of survival to the juvenile stage an additional 65–87%.…”
Section: Discussionmentioning
confidence: 75%
“…These forms all start their benthic lives as single polyps, which we refer to as primary polyps. Primary polyps are unambiguously recruits and some species can start budding new polyps within weeks of metamorphosis ( Tonra, Wells & Lasker, 2021 ), but some may take months ( Hwang & Song, 2007 ; Sun, Hamel & Mercier, 2011 ). Most studies of recruitment among octocorals have sampled on scales greater than the time needed for many recruits to bud, and therefore have included small single branch colonies as recruits, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sea tables, P. homomalla started releasing eggs between 21:00 and 21:30, with different colonies (males and females) starting at different times over a 60 min period. Release continued for approximately 2 h. Eggs collected during the spawning events developed into planulae which successfully settled (see Tonra et al 2021 for more details).…”
Section: Reproductionmentioning
confidence: 99%